Effects of reducing inspired oxygen concentration for one hour in patients with chronic heart failure: implications for air travel. (May 2013) - Hobkirk, James P.; Damy, Thibaud; Walters, Mandy; Bennett, Anna; Smith, Sarah J.; Ingle, Lee; Clark, Andrew L.; Cleland, John G.F.
<x xml:space="preserve">Abstract</x> Aims The objective of this study was to establish the acute effects of hypoxia on clinical, spirometric, haemodynamic, and echocardiographic variables. Reducing inspired oxygen to 15%, as experienced during commercial air travel, decreases arterial oxygen saturation, increases respiratory rate and pulmonary artery pressure in healthy subjects. The effect on patients with chronic heart failure is unknown. Methods and results Seventy‐two patients with chronic heart failure and an LVEF <40%, in NYHA functional class II (74%) or III (26%), on stable treatment were studied and compared with 18 age‐matched controls (65 ± 11 vs. 62 ± 12 years, respectively). Clinical, spirometric, haemodynamic, and echocardiographic measurements were performed in patients and controls before and after one hour inspiring 15% oxygen. Inspired 15% oxygen for 1 h was tolerated in all subjects and caused no worsening of symptoms. Arterial oxygen saturation decreased to a similar extent in patients (from 97 ± 2% to 86 ± 4%) and controls (from 97 ± 2% to 86 ± 3%). Mean arterial pressure increased from 81 ± 13 mmHg to 87 ± 12 mmHg in patients, but did not change in controls. There was no effect on heart rate, but systolic pulmonary artery pressure rose from 30.2 ± 14.0mmHg to 34.0 ± 15.2 mmHg in patients, and from 22.4 ± 5.5 mmHg to 24.1 ± 6.9 mmHg in controls. Conclusions Inspiring 15% oxygen was tolerated and caused no worsening of symptoms despite reductions in arterial oxygen saturation and increases in mean arterial pressure and systolic pulmonary artery pressure.